Association of remnant cholesterol with cognitive impairment: a cross-sectional study - Bai, Weili; He, Yong; Xiao, Xuewen; Zhu, Tieshi (Frontiers in Human Neuroscience, 2026)
BackgroundAlthough dyslipidemia has been implicated in the development of cognitive impairment, the association between remnant cholesterol (RC) and cognitive outcomes remains incompletely understood.MethodsWe conducted a cross-sectional study using data from 1,136 participants at Liuyang Jili Hospital from 2022. RC was calculated as total cholesterol minus low-density and high-density lipoprotein cholesterol, and cognitive function was assessed using the Mini-Mental State Examination. Restricted cubic spline and multivariable logistic regression models were used to evaluate associations between RC and cognitive impairment, with subgroup, and sensitivity analyses. Machine learning models with SHapley additive explanation (SHAP) values were applied to assess variable importance.ResultsParticipants had a median age of 68 years, and 21.2% had cognitive impairment. Higher RC levels were associated with increased risk of cognitive impairment (per 1-mmol/L increase: adjusted odds ratio, 3.47; 95% CI, 2.34–5.25; P < 0.01), with no evidence of a non-linear relationship. The association remained consistent across subgroups. In machine learning analyses, RC ranked third in variable importance after waist circumference, and body mass index, and SHAP dependency plots demonstrated a monotonic positive relationship between RC and cognitive impairment risk.ConclusionElevated RC levels are positively associated with an increased risk of cognitive impairment. These findings suggest that remnant cholesterol may be an important and modifiable risk factor for cognitive dysfunction, warranting confirmation in prospective longitudinal studies.